KEWENANGAN PEMERINTAH KABUPATEN BENGKAYANG DALAM PENGELOLAAN PASAR (Sudi Pasar Tengah Kecamatan Bengkayang) - Marvolomeus Pane 42009043 (GOVERNANCE, Jurnal Ilmu Pemerintahan, 2022)
This thesis is intended to describe the management authority and the market barriers which become obstacles in the implementation of market management authority . This thesis was appointed by the problems occurred , which is not the maximum performance of duties in managing market.Therefore the analysis is done by using the theory of R. Terry is with the concept of management planning, organizing ,mobilizing and monitoring. The conclusion of this research is maximal in the management market which resulted into a disorderly market . The lack of disorderly market due to problems of placement fruit market traders conducted by the local government because of the limited land available in the market and the shortage of human resources required . Keywords : authority and market management.